Theoretical underpinnings of a need-supportive intervention to address sustained healthy lifestyle changes in overweight and obese adolescents - Fenner, Ashley; Straker, Leon; Davis, Melissa; Hagger, Martin (Elsevier BV, 2013)
Objectives: Recent figures indicate that nearly a quarter of Australian adolescents are overweight or obese. Despite the well-established role of physical activity and healthy eating in reducing prevalence of obesity, there remains a lack of effective interventions that promote sustained behavior engagement. This paper aims to describe the theory-based integration and implementation of self-determination theory and goal setting theory in a family-based lifestyle intervention. Although these theories have been shown to independently predict motivation for behavior, a limited number of studies have described behavior-change techniques at a level to allow for effective evaluation and replication, and no studies have combined the theories in a healthy lifestyle behavior intervention. Methods: Behavior change techniques and the associated change mediators are described in relation to need-supportive environments provided by instructors and extended to parents in the home environment. Methods for motivating and promoting sustained engagement in adolescent physical activity and healthy eating and parent behaviors to support these lifestyle changes are discussed within the context of need-satisfaction and goal setting. Conclusions: This study will contribute to understanding processes for developing and implementing behavior-change techniques based on the integration of two theories of motivation. Future interventions aimed at promoting maintenance of physical activity and healthy eating behaviors in overweight and obese adolescents will benefit by being informed of which techniques are effective at enhancing motivation within the intervention context and home environment.